The effect of acute topiramate administration on morphine withdrawal syndrome and brain-derived neurotrophic factor in central nervous system. - CABADAK, HÜLYA (My University, 2023)
Objectives: Nucleus accumbens plays an important role in opioid addiction. Topiramate, increases postsynaptic gamma-aminobutyric acid receptor activity and antagonizes glutamatergic activity. Brain-derived neurotrophic factor (BDNF), which plays a key role in synaptic plasticity, is produced from proBDNF. The aim of this study is to investigate the effects of 100 μM topiramate applied into the lateral ventricle or nucleus accumbens on naloxone-induced morphine withdrawal and the BDNF/proBDNF ratio in the frontal cortex. Methods: In the study, 36 adult male Wistar rats weighing 250–350 g were used. Morphine dependence was created with morphine pellets following guide cannula implantations. Withdrawal findings were evaluated in naloxone-induced morphine withdrawal syndrome following topiramate administration, and locomotor activity measurements were performed simultaneously. The brains of sacrificed animals were removed for determination of BDNF/ proBDNF ratio. Results: Topiramate administered by either route significantly suppressed the number of jumps in morphine withdrawal. Topiramate applied into the nucleus accumbens significantly reduced stereotypical behavior in morphine withdrawal, but did not cause any changes in other locomotor activity behaviors. Topiramate applied into the lateral ventricle significantly decreased the BDNF/proBDNF ratio, whereas administered into the nucleus accumbens significantly increased this ratio. Conclusion: The findings of this study indicate that topiramate administered into the lateral ventricle and nucleus accumbens reduces naloxone-induced morphine withdrawal symptoms, stereotypical locomotor activity, and changes the BDNF/proBDNF ratio.
Keywords: Anticonvulsant; mBDNF; nucleus accumbens; opioid; proBDNF